4, 5‐Dinitrosulfonefluorescein and related dyes: Kinetics of reversible rupture of the pyran ring and their interaction with lysozyme. (23rd June 2021) - Kriklya, Nika N.; Gromovoy, Taras Yu.; Mchedlov‐Petrossyan, Nikolay O.
Abstract: Fluorescein and sulfonefluorescein dyes are stable in solution within a wide pH range. Nucleophilic addition of the hydroxide (HO – ) group to the nodal carbon atom is not typical of these compounds. They are also not prone to rupture of the pyran cycle under the action of alkali. However, the last‐named heterocycle readily opens at high pH values in the case of derivatives containing nitro groups in the xanthene moiety. Moreover, while in the case of nitrofluoresceins, for example, 4, 5‐dinitrofluorescein, this reaction is irreversible, with 4, 5‐dinitrosulfonefluorescein acidification of the alkaline solution immediately returns the visible absorption spectrum to that of the original hydroxyxanthene dye. We present a quantitative study of the kinetics of the pyran cycle rupture in aqueous alkali without and with micelles of a cationic surfactant. Also, both initial dye and reaction product were studied via the matrix‐assisted laser desorption/ionisation time‐of‐flight (MALDI‐ToF) technique. The second part of the article is devoted to the interaction of 4, 5‐dinitrosulfonefluorescein and other dyes of similar structure with lysozyme basing on the MALDI‐ToF mass spectrometry. This made it possible to arrange the dyes according to their affinity for the protein and draw some conclusions about the nature of the association of the dye with lysozyme.